Android wireless control system / Muhammad Aminur Rashid Mohd Dalil & Mohamad Nor Mahful Hussin - Mohd Dalil, Muhammad Aminur Rashid; Mahful Hussin, Mohamad Nor Mahful (2015)
The basis of this project was to create Android wireless control system. The idea was to make our work much easier. By using this project we can control the other thing with using our own android smart phone. We choose wireless system is because it much better than the Bluetooth. Wireless system also have their own security, so our project not easily can be disturb by others during the system running. Android wireless control system is a system where it is can be use to control other devices with using wireless medium which is WiFi operator at 2.4 GHz. The examples are lawn motor, cars and other. Nowadays, most people have their own android devices thus with this system it will make people life more easier with controlling other devices while they rest